2004
DOI: 10.1248/bpb.27.52
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium Diclofenac on Serum and Tissue Concentration of Amoxicillin and on Staphylococcal Infection

Abstract: Amoxicillin is a widely prescribed aminopenicillin, primarily for oral use.1) Ninety percent of the administered dose is absorbed without molecular modifications.2) It provides human serum concentration ranging from 7.6 mg/ml to 10.8 mg/ml when 500 mg/p.o. is used 3,4) ; 15.1 mg/ml when 15.4 mg/kg/p.o. is used, 1) and 14.5 mg/ml when 40 mg/kg/p.o. is used.5) The serum concentrations in rats were 28 mg/ml and 13 mg/ml when amoxicillin doses of 40 mg/kg/p.o. and 7.0 mg/kg/p.o. were administered, respectively. 6,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 25 publications
5
17
0
2
Order By: Relevance
“…It is well stablished that bacteria growing in tissues surrounded by immune cells show slow reproduction, which decreases the penicillin activity. 17 …”
Section: Discussionmentioning
confidence: 99%
“…It is well stablished that bacteria growing in tissues surrounded by immune cells show slow reproduction, which decreases the penicillin activity. 17 …”
Section: Discussionmentioning
confidence: 99%
“…Diclofenac has been shown to significantly reduce S. aureus counts from rat granulomatous tissue in the absence of antibiotic [16]. This observation might result from host-specific effects (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The NSAID diclofenac is antibacterial in vitro , and administration to mice or rats infected with Listeria monocytogenes, Salmonella typhimurium, Mycobacterium tuberculosis or S. aureus has been reported to significantly reduce bacterial pathogen cell counts in blood and in organ homogenates [16-18]. Growth of E. coli with inhibitory concentrations (2 × MIC or 100 μg/ml) of diclofenac was shown to reduce the rate of Ci ( 3 H) deoxythymidine incorporation into DNA, indicating that diclofenac may target DNA biosynthesis [19].…”
Section: Introductionmentioning
confidence: 99%
“…Groppo et al [14] demonstrated that sodium diclofenac could significantly reduce amoxicillin blood levels in rats, which was probably not caused by interference with metabolism or renal excretion, since amoxicillin and diclofenac have different pharmacokinetics (plasma protein binding, excretion and metabolism).…”
Section: Discussionmentioning
confidence: 99%
“…Co-administration of amoxicillin with NSAIDs is common in dentistry and medicine [13]. A previous study in rats showed that both amoxicillin tissue and serum concentrations were significantly reduced by sodium diclofenac [14].…”
Section: Introductionmentioning
confidence: 99%